MEWUJUDKAN KEAMANAN INSANI DARI ANCAMAN NON-TRADISIONAL: PENCEGAHAN COVID-19 DI PASAR MINGGU DESA KOTA TENGAH - Luerdi Luerdi; Rahmadi Khaidir; Novi Dian Sari Nasution; Widia Anggraini; Nabilah Nabilah; Muhammad Rozi Muharpan (Universitas Majalengka, 2020)
This community service program aimed to realize human security from the threat of COVID-19 pandemy by conducting preventive attempts at the Pasar Minggu, Village of Kota Tengah, Subdistrict of Kepenuhan, District of Rokan Hulu. Insufficient literacy on the pandemic and very limited numbers of prevention facilities in the market encouraged the community service. The activitiy was carried out for more and less two weeks in the form of socializing and providing equipment. The program had a number of work plans such as informing the danger and threat of COVID-19, setting up a banner encouraging people to implement health protocol and providing public hand-washing facilities. Such program is expected to help to cut off the swift spread of COVID-19 in the non-urban areas especially those located in the Village of Kota Tengah.